A method for developing structure-rheology relationships in comminuted plant-based food and non-ideal soft particle suspensions. (November 2019) - Boehm, Michael W.; Warren, Frederick J.; Baier, Stefan K.; Gidley, Michael J.; Stokes, Jason R.
Abstract: Particles can pack to give progressively increasing suspension viscosity, and, once packed beyond some critical value, the bulk sample exhibits elasticity due to steric interactions between the volume-occupying particles. Comminuted and hydrated plant-based foods are particularly interesting because they comprise "particles" in the form of plant cells, cell clusters & cell pieces and released cell contents such as starch granules, which can hydrate, swell and thereby interact. Here, we present rheological data for boluses made by mixing comminuted fried carrot chips, raw uncooked carrots or fried potato chips with water. These example foods comminute into non-spherical particles with a range of sizes, e.g., above 2 mm to less than 700 μm, yet the underlying physics controlling the bulk rheology are the same in all cases, namely that of volume occupying interacting particles. If particles are considered hard spheres with a known density, the calculation of particle phase volume is trivial; however, this is not the Case for comminuted plant tissues. Thus, measuring the phase volume for most food particles and model soft particles has been historically difficult due to swelling/de-swelling. We describe here how a gravity-controlled settling experiment, using only Earth's natural gravity, can be used to determine a settling parameter, SR, which can then be used to adjust weight fraction thereby providing a measure of phase volume. We show its utility by estimating the random close packing phase volume of ideal hard spheres, which compare favorably with known and independently measured values. Finally, we use our settling technique to measure the settling parameter then perform a mathematical adjustment to the solids mass fraction, which we show results in a collapse of the rheological data for boluses comprising non-ideal soft food particles. Graphical abstract: Image 10162 Highlights: Present a simple technique for calculating a settling ratio. Illustrate how the settling ratio is related to the particle phase volume. Present a step towards a universal scaling in rheological data for plant-based cell suspensions. Calculating the settling ratio of plant based cell suspensions and small strain oscillatory rheological data. Insights to plant-based simulated boli and their settling behavior and rheological behavior.